MITOCHONDRIAL-DERIVED PEPTIDES: NOVEL HORMONES THAT REGULATE METABOLISM DURING AGING. (11th November 2018) - Cohen, P
Abstract: Mitochondrial-Derived-Peptides (MDPs) are novel peptides encoded within the mtDNA that serve as signals for cell and organismal protection and energy expenditure. The MDP family includes humanin and SHLPs encoded from the 16S rRNA region and have broad protective effects and one called MOTS-c which is encoded from the 12S rRNA region and has potent anti-obesity effects and prevents the development of hepatic steatosis. MDPs have been administered to various disease models and delay the progression of atherosclerosis, Alzheimer's and chemotherapy-induced side-effects. Plasma Humanin, SHLP2, and MOTS-c fall with age, and their levels correlate with endothelial function and various from diseases prostate cancer to Alzheimer's. MDP levels are also upregulated by diet and exercise. MDPs are expressed in an ethno-specific fashion and may contribute to health disparities in a manner related to relevant mitochondrial DNA SNPs. Several MDPs are in various stages of preclinical development for diseases of aging.